The Influence of Mobile Banking Service Quality on Customer Satisfaction at Bank Rakyat Indonesia Tanjung Karang Branch Office - Rahmad Sucandra; Dora Rinnova (Cita konsultindo, 2024)
This research investigates the influence of mobile banking service quality on customer satisfaction at the Tanjung Karang Branch Office of Bank Rakyat Indonesia (BRI). With the rapid growth of information technology, mobile banking has become a crucial element in banking service strategy. The focus of this research is to identify the extent to which service quality dimensions, including reliability, responsiveness, security, ease of use, and mobile banking functionality, influence customer satisfaction. The research method uses a quantitative approach by distributing questionnaires to BRI customers at the Tanjung Karang Branch Office. Data analysis was done using statistical techniques, including correlation and coefficient of determination tests. The results of this research hope to provide in-depth insight into the extent to which the quality of mobile banking services can increase customer satisfaction in the local banking environment. The conclusion from this research is that service quality positively influences customer satisfaction. It is hoped that the findings of this research can contribute to Bank Rakyat Indonesia to optimize its mobile banking service strategy so that it can meet customer expectations and needs. It is also hoped that the practical implications of the research findings will help Bank Rakyat Indonesia strengthen its position in the competitive banking market by maintaining and increasing customer satisfaction.